2002
DOI: 10.1007/s00390-002-0312-9
|View full text |Cite
|
Sign up to set email alerts
|

Measuring intra-abdominal pressure in the intensive care setting

Abstract: Increased intra-abdominal pressure (IAP) may occur in critically ill patients. The easiest method to estimate IAP at the bedside is the bladder pressure measurement. A standard procedure (same volume infused, pressure transducers, and patient's position) should be used to obtain comparable and reproducible data among different patients and during different stages and time of the disease. The increase in IAP leads to two major pathological conditions: 1) the intraabdominal hypertension (IAP above 16 cmH2O) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Second, this site was chosen to allow for more accurate measurement of intra‐abdominal hypertension. Previous work has shown that the mass of the abdominal contents above the site of measurement influences the intra‐abdominal pressure measured 2,6,20,21 . Because the majority of gastrointestinal viscera lies beneath the cannula, the site selected should reduce error due to normal variations in abdominal fill, but still allow space above the cannula to measure any abnormal increase in intra‐abdominal pressure in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, this site was chosen to allow for more accurate measurement of intra‐abdominal hypertension. Previous work has shown that the mass of the abdominal contents above the site of measurement influences the intra‐abdominal pressure measured 2,6,20,21 . Because the majority of gastrointestinal viscera lies beneath the cannula, the site selected should reduce error due to normal variations in abdominal fill, but still allow space above the cannula to measure any abnormal increase in intra‐abdominal pressure in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…A pathological increase in pressure in the abdomen is described as intra‐abdominal hypertension in humans, and is defined by sustained or repeated measures of intra‐abdominal pressure >12 mm Hg 1 . With increased intra‐abdominal pressure, venous return and cardiac output decrease, and tissue perfusion is reduced 1,2 . Intra‐abdominal hypertension is an independent risk factor for multiple organ dysfunction, and organ failure resulting from intra‐abdominal hypertension is known as abdominal compartment syndrome 1,3 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By decreasing venous return, intra‐abdominal hypertension may cause venous pooling and stasis, which predisposes to venous thrombo‐embolic disease. Appropriate mechanical and pharmacological measures must be taken to decrease the risks of pulmonary embolism [24].…”
Section: Cardiovascularmentioning
confidence: 99%
“…As the volume within the abdominal cavity increases, the compliance tends to decrease, eventually resulting in exponential increases in intraabdominal pressure for minor changes in intraabdominal volume 1,2 . This loss of compliance along with abnormally high intraabdominal pressure is termed intraabdominal hypertension 1,3–5 …”
Section: Introductionmentioning
confidence: 99%